The Impact of Body Composition on Wound Healing in Type 2 Diabetes Patients: A Systematic Review - Sulfikar, Andi; Mulyati, Mulyati; Hasni, Hasni; Taher, Rusli; Lukman, Sartika; Muhammadong, Muhammadong; Tobang, Rindani Claurita; Restika BN, Indah (Media Publikasi Cendekia Indonesia, 2025)
Wound healing in patients with type 2 diabetes mellitus (T2DM) presents a major clinical challenge, particularly due to alterations in body composition such as reduced muscle mass and increased fat mass. This systematic review aimed to synthesize current evidence regarding the impact of body composition on wound healing effectiveness in T2DM patients. Literature was retrieved from PubMed, ProQuest, Wiley Online Library, and Google Scholar, targeting observational and experimental studies published between 2015 and 2025. Keywords included